DEVELOPMENT OF A RISK MANAGEMENT STRATEGY IN MACHINE BUILDING IN ORDER TO ENSURE A TARGETED LEVEL OF QUALITY - Юнг, Екатерина; Кабаргина, Наталья; Воронцова, Алла (SWorldJournal, 2021)
The paper considers a modern approach to quality management through a risk management system, proposed in the version of the ISO 9001: 2015 standard, which involves the combination of a Quality Management System and a Risk Management System.In the transi